2008
DOI: 10.1111/j.1532-5415.2008.01766.x
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Falls and Dual Task–Related Decrease in Walking Speed: Is There a Relationship?

Abstract: Slower walking speed while counting backward was associated with recurrent falls, suggesting that changes in gait performance while dual tasking might be an inexpensive way of identifying frail older adults prone to falling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
120
2
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(131 citation statements)
references
References 24 publications
(75 reference statements)
6
120
2
3
Order By: Relevance
“…4 Elderly individuals have shown an inability to adapt their walking pattern to unexpected situations in their daily lives, which usually occur when performing several simultaneous tasks. [4][5][6] The dual-task (DT) paradigm has been in use since the middle of the 1980s and involves the performance of two concomitant tasks. It was first used in psychological studies and was later adopted by health professionals working in the areas of rehabilitation and gerontology to assess and train elderly individuals in a secondary task, with walking as the primary task.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Elderly individuals have shown an inability to adapt their walking pattern to unexpected situations in their daily lives, which usually occur when performing several simultaneous tasks. [4][5][6] The dual-task (DT) paradigm has been in use since the middle of the 1980s and involves the performance of two concomitant tasks. It was first used in psychological studies and was later adopted by health professionals working in the areas of rehabilitation and gerontology to assess and train elderly individuals in a secondary task, with walking as the primary task.…”
Section: Introductionmentioning
confidence: 99%
“…4,14 The aging process is accompanied by alterations in the spatial and temporal parameters of gait, 14 such as reductions in gait speed and step length, as well as increases in step variability, double support time and step width, 4,12,15 all of which have been correlated with a higher incidence of falls. 5,6,[16][17][18][19][20][21] An assessment of these parameters is generally used to identify abnormalities in an individual's gait. 22 While several gait parameters (reduced speed, reduced step length and increased double support time) can reflect impairment and are correlated with a fear of falls, step variability is the indicator that provides the best representation of postural instability.…”
Section: Introductionmentioning
confidence: 99%
“…Different outcome parameters from DT walking indicating a fall risk were the following: reduced walking speed, 18 changes in step width, step time, and step length, 17 or variability in stride time. 19 In chronic stroke patients, Hyndman et al 15 found that Fs showed a significantly reduced stride length during DT gait analyses compared with NFs.…”
Section: Archives Of Physical Medicine and Rehabilitationmentioning
confidence: 99%
“…Current stroke patient rehabilitation assessments, whether in a clinic or at home, involve subjective, task orientated assessments. Whilst these are useful, visual observation alone cannot sufficiently characterise subtle changes to gait [3]. This is an important consideration as the progress of patient rehabilitation will inform the direction and continuation of physical therapy interventions, particularly if those interventions are home-based.…”
Section: Introductionmentioning
confidence: 99%